Use of CAR-T cells for the treatment of relapsed and refractory multiple myeloma: a systematic review - Sakamoto, Satchie; Sgnaolin, Vanessa (Brazilian Journal of Oncology, 2024)
A systematic review of published articles based on randomized clinical trials was conducted to ascertain the efficacy or perspective of using CAR-T cell therapy for refractory multiple myeloma. The PubMed database was searched with the combination of terms “multiple myeloma”, “refractory multiple myeloma”, “CAR T-cell”, and the PRISMA criteria were followed. Of the 78 articles found, only 5 were selected. The studies used different treatment protocols and four different types of CAR-T cells. All studies obtained interesting results in terms of increased progression-free survival and negative minimal residual disease responses. Some authors detected an expansion of CAR-T cells and noted dose-dependent relationship between treatment effectiveness and serum BCMA levels. Although the results were promising, a small number of patients still relapsed a few months after CAR-T cell infusion. Therefore, this new line of therapy should be further investigated, as it significantly increases progression-free survival and improves quality of life.
Keywords: Multiple myeloma; Immunotherapy, Adoptive; B-cell maturation antigen; Recurrence